Three new species of the Phaonia acerba group (Diptera: Muscidae) from Palaearctic and Oriental Regions - Yu, Teng; Xue, Wan-Qi (Entomologica Fennica, 2015)
Three new species of the Phaonia acerba group fromthe Palaearctic and Oriental Regions are described: P. gaoligongshanensis Xue & Yu, sp. n., P. zhangxianggi Xue & Yu, sp. n. and P. hongkuii Xue & Yu, sp. n. An identification key to the males of 8 species of the Phaonia acerba group from the Palaearctic and Oriental Regions is provided.